The scale validation of public participation of renewable energy (RE) development in Malaysia: An exploratory factor analysis (EFA) - Wan Abdullah W.M.Z.; Zainudin W.N.R.A.; Mohamad Ishak W.W. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS